NESTING AND BREEDING ECOLOGY OF MARINE TURTLE IN ST. MARTIN'S CORAL ISLAND, BANGLADESH - Hossain, M.L.; Jaman, M.F.; Sarker, S.U.; Mahmood, S.U. (Ecoprint: An International Journal of Ecology, 2004)
Observations on nesting and breeding ecology of three species of marine turtle were made in St. Martin's Island, Bangladesh. The egg laying period was found to be in winter season between October and March. The peak breeding period was in December and January. The mean diameter of the nests of Olive ridley turtle, Lepidochelys olivacea was 27.42 ± 5.2 cm. Green turtle, Chelonia mydas 25.67 ± 1.53 cm and Loggerheaded turtle, Caretta caretta 27.65 ± 1.52 cm. The mean depth of nest of L. olivacea was 49.17 ± 5.61 cm, C. mydas 51 ± 2.65 cm and C. caretta 54.33 ± 1.53 cm. Mean clutch size of L. olivacea was 115.6 ± 16.7 eggs, C. mydas 112.15 ± 11.52 eggs and C. caretta 122 ± 18.62 eggs. The mean weight of eggs of L. olivacea was 31.63 ± 1.83. C. mydas 32.71 ± 1.26 and C, caretta 32.45 ± 3.75, Mean incubation period of L. olivacea was 63.9 ± 3.5 days, C. mydas 61.85 ± 2.57 days and C. caretta 61.5 ± 1.29 days. The mean hatching success of L. olivacea was 81.14%, C. mydas was 80.11%, and C. caretta 84.43%. The mean weight of hatchlings of L. olivacea was 14.7 ± 0.58g, C. mydas 15.4 ± 0.78 g and C. caretta 16.20 ± 0.3 5 g. Loss of nesting ground by the local people and visitors and poaching of eggs and injured of mother turtles by the dogs was the main problems for breeding of turtles on this island. Construction of embankments for control of erosion, destruction of nests by indigenous dogs and monitor lizards should be protected. Immediate conservation measures are warranted to save the breeding of turtles on this island.Key words: Nesting, breeding, ecology, marine turtles, conservation.Ecoprint Vo.11(1) 2004.